Technology-enhanced multimodal approaches in classroom L2 pronunciation training - Toyama, Michiko; Hori, Tomoko (Frontiers in Education, 2025)
Advances in L2 pronunciation instruction have embraced technology-enhanced multimodal approaches, engaging auditory, visual, and kinesthetic modalities to create interactive, immersive learning environments. This review examines three key methods: gesture-based techniques, speech visualization tools, computer-assisted pronunciation training. These approaches visualize auditory and articulatory features, reinforce prosody, or offer real-time feedback, enhancing learner engagement and retention. Despite their potential, challenges such as accessibility, technical limitations, and pedagogical integration remain. This review highlights the transformative potential of multimodal methods in L2 pronunciation training and outlines directions for future research and innovation.